Head and neck giant keratoacanthoma: a case report - De Souza Damasceno, Yuri Edward; Souza de Carvalho, Waldner Ricardo; Neto, Nicolau Conte; Vieira, Eduardo Hochuli [UNESP]; Lacerda de Souza, Lucas; Rebelo Pontes, Hélder Antônio (Sociedade Portuguesa de Estomatologia e Medicina Dentaria (SPEMD), 2018)
Keratoacanthoma is a low-grade tumor originated from the pilosebaceous glands that nearly resembles squamous cell carcinoma under histopathological analysis. Giant keratoacanthoma is a rare subtype with a size exceeding 2 cm, with a high aggressiveness potential. Head and neck giant keratoacanthomas are uncommon and mainly affect male patients with a mean age of 59.1 years old, usually affecting the nose. Excision of the lesion is the preferred treatment for giant keratoacanthoma. The aim of this study is to analyze the clinicopathological characteristics of head and neck giant keratoacanthoma by reviewing the previously published English literature and reporting one new case of a rare lesion affecting the lower lip.
Keywords: Excision; Giant keratoacanthoma; Treatment